In Vitro and in Vivo Evaluation Of Pharmacological Activites of Pouzolzia Sanguinea (Journal of Bio-Science, 2021)
Pouzolzia sanguinea grows in tropical and sub-tropical regions of Bangladesh, used for a variety of purposes including pain, rheumatoid kidney diseases in traditional medicine. The crude ethanolic leaf extract of P. sanguinea with its different fractions (ethanol, n-hexane, and chloroform) was investigated for phytochemical constituents, in vitro antioxidant, anti-inflammatory effects, in-vivo analgesic and antipyretic activities. Preliminary phytochemical constituents were identified by chemical group test. P. sanguinea fractionated extracts contain alkaloids, glycosides, tannins, flavonoids, saponins, gums, and amides. Antioxidant activity test was performed by both qualitative (TLC and Rf value) and quantitative tests (inhibition of DPPH free radical scavenging). Extracts exhibited significant (p